Risk factors for acute GVHD and survival after hematopoietic cell transplantation - Jagasia, Madan; Arora, Mukta; Flowers, Mary E D; Chao, Nelson J; McCarthy, Philip L; Cutler, Corey S; Urbano-Ispizua, Alvaro; Pavletic, Steven Z; Haagenson, Michael D; Zhang, Mei-Jie; Antin, Joseph H; Bolwell, Brian J; et al. (Blood, 2012)
Risk factors for acute GVHD (AGVHD), overall survival, and transplant-related mortality were evaluated in adults receiving allogeneic hematopoietic cell transplants (1999-2005) from HLA-identical sibling donors (SDs; n = 3191) or unrelated donors (URDs; n = 2370) and reported to the Center for International Blood and Marrow Transplant Research, Minneapolis, MN. To understand the impact of transplant regimen on AGVHD risk, 6 treatment categories were evaluated: (1) myeloablative conditioning (MA) with total body irradiation (TBI) + PBSCs, (2) MA + TBI + BM, (3) MA + nonTBI + PBSCs, (4) MA + nonTBI + BM, (5) reduced intensity conditioning (RIC) + PBSCs, and (6) RIC + BM. The cumulative incidences of grades B-D AGVHD were 39% (95% confidence interval [CI], 37%-41%) in the SD cohort and 59% (95% CI, 57%-61%) in the URD cohort. Patients receiving SD transplants with MA + nonTBI + BM and RIC + PBSCs had significantly lower risks of grades B-D AGVHD than patients in other treatment categories. Those receiving URD transplants with MA + TBI + BM, MA + nonTBI + BM, RIC + BM, or RIC + PBSCs had lower risks of grades B-D AGVHD than those in other treatment categories. The 5-year probabilities of survival were 46% (95% CI, 44%-49%) with SD transplants and 33% (95% CI, 31%-35%) with URD transplants. Conditioning intensity, TBI and graft source have a combined effect on risk of AGVHD that must be considered in deciding on a treatment strategy for individual patients.